2016
DOI: 10.1179/1743132815y.0000000089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dose–effect and therapeutic time window in preclinical studies of rhEGF and GHRP-6 coadministration for stroke therapy

Abstract: The coadministration of rhEGF and GHRP-6 at doses of 100 and 600 μg/kg, respectively, administered up to 4 hours following the ischaemic insult, significantly improved survival and neurological outcome, and reduced infarct volume compared with vehicle treatment. These results are considered as an additional proof of concept as supporting a combined therapeutic approach and justify the further development of this preclinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…In this study, the positive and significant correlation between time to treatment and mRS suggests that earlier intervention with EGF+GHRP6 may decrease disability 6 months after the onset of symptoms. This finding is also consistent with our pre-clinical studies ( 19 ). Although the immediate intervention is likely to enhance the therapeutic effects, we anticipate that components of this combination therapy will also target later secondary events, promoting survival of the neurovascular unit and activating endogenous neuroprotective pathways, which would predict a longer-lasting effect ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, the positive and significant correlation between time to treatment and mRS suggests that earlier intervention with EGF+GHRP6 may decrease disability 6 months after the onset of symptoms. This finding is also consistent with our pre-clinical studies ( 19 ). Although the immediate intervention is likely to enhance the therapeutic effects, we anticipate that components of this combination therapy will also target later secondary events, promoting survival of the neurovascular unit and activating endogenous neuroprotective pathways, which would predict a longer-lasting effect ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 94%
“…The EGF+GHRP6 combined therapy for stroke was designed to activate a cascade of endogenous neuroprotection mechanisms, including regeneration of adult neural stem cells and repair in the penumbra zone ( 26 31 , 57 , 71 , 72 ). The activation of these pathways could explain the clinical (neurological, functional, and survival) outcomes evidenced in this study, which had been previously demonstrated in stroke animal models ( 17 19 ). The events induced by both active agents in this combined therapy have a scope that transcends beyond the acute phase of brain infarction ( 57 , 71 , 73 , 74 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Fortunately, synthetic ghrelin analogs offer prolonged stability, significant plasma release for up to 24 h, oral bioavailability and the ability to co-bind CD36, which may be useful to diminish Aβ-driven microglial inflammation (Bulgarelli et al, 2009;Muller et al, 2015;Berlanga-Acosta et al, 2017). To further enhance efficacy, the combination of ghrelin agonists with other growth factors, such as EGF (Barco et al, 2011, del Barco et al, 2011 Barco-Herrera et al, 2013;Subiros et al, 2016), GH (Wu et al, 2009b;Zhou et al, 2017), insulin (Granado et al, 2011) and GLP-1 (Duarte et al, 2018), or DAG, to prevent AGencouraged glucose intolerance and hypoinsulinemia (Gauna et al, 2004;Kiewiet et al, 2009), may be profitable. On the other hand, due to the possible development of ghrelin resistance in AD and reports of gastrointestinal complications in some PD patients, clinical studies are warranted to monitor the longterm effectiveness of AG.…”
Section: Resultsmentioning
confidence: 99%
“…56 Garcia del Barco and coworkers in our group have opened unprecedented avenues, by combining GHRP-6 and EGF as a therapeutic approach to ameliorate the damages of multiple sclerosis, 57 peripheral axonal pathology, 58 and brain ischemia in animal models. 59 , 60 They have demonstrated that in all these experimental substrates the combined action of GHRP-6 and EGF is associated with a better outcome in both clinical and pathological fields.…”
Section: Pharmacological Repositioning Of Ghrpmentioning
confidence: 99%